Potential of gamma/delta T cells for solid tumor immunotherapy - Zhu, Dantong; Ren, Xijing; Xie, Wanting; Chen, Jianjun; Liang, Shiying; Jiang, Mingzhe; Wang, Junyi; Zheng, Zhendong (Frontiers in Immunology, 2024)
Gamma/delta T (γδ T)cells possess a unique mechanism for killing tumors, making them highly promising and distinguished among various cell therapies for tumor treatment. This review focuses on the major histocompatibility complex (MHC)-independent recognition of antigens and the interaction between γδ T cells and solid tumor cells. A comprehensive review is provided regarding the classification of human gamma-delta T cell subtypes, the characteristics and mechanisms underlying their functions, as well as their r545egulatory effects on tumor cells. The involvement of γδ T cells in tumorigenesis and migration was also investigated, encompassing potential therapeutic targets such as apoptosis-related molecules, the TNF receptor superfamily member 6(FAS)/FAS Ligand (FASL) pathways, butyrophilin 3A-butyrophilin 2A1 (BTN3A-BTN2A1) complexes, and interactions with CD4, CD8, and natural killer (NK) cells. Additionally, immune checkpoint inhibitors such as programmed cell death protein 1/Programmed cell death 1 ligand 1 (PD-1/PD-L1) have the potential to augment the cytotoxicity of γδ T cells. Moreover, a review on gamma-delta T cell therapy products and their corresponding clinical trials reveals that chimeric antigen receptor (CAR) gamma-delta T therapy holds promise as an approach with encouraging preclinical outcomes. However, practical issues pertaining to manufacturing and clinical aspects need resolution, and further research is required to investigate the long-term clinical side effects of CAR T cells. In conclusion, more comprehensive studies are necessary to establish standardized treatment protocols aimed at enhancing the quality of life and survival rates among tumor patients utilizing γδ T cell immunotherapy.